Developing a cross-cultural conceptual model for testing organisational commitment in the UAE: a theoretical perspective. (1st November 2007) - Anwar, Syed Aziz; Chaker, Mohammad Naim; Ferhat, Nadia Rifat
The motivations for international business firms to seek unimpeachable commitment of their employees for attaining the avowed organisational objectives in various parts of the world have been one of the cornerstones of managerial action and contemporary research. However, organisational commitment in a cross-cultural context of an open Arabian economy such as the United Arab Emirates (UAE) has not been studied adequately, presumably partly owing to lack of conceptual clarity and partly due to lack of empirical information. The main objective of this study is to present a conceptual model of testing organisational commitment in a cross-cultural context of the UAE and explore its implications for managerial decisions.